Study and development of novel composite materials for the application of car brake rotor - Fu, Ping Rong Kimberly (Curtin University, 2014)
From experimental study of properties including density, tensile strength, Young’s modulus, fracture toughness for both aluminium alloy reinforced with silicon carbide and aluminium alloy reinforced with alumina representing metal matrix composites, and measurements of compressive strength for the above composites and alumina and aluminium titanate based ceramics as functionally graded materials, together with estimated thermal conductivity and specific heat capacity, show promising results for the use of these materials for car brake rotor.